Optimalisasi Pengelolaan Zakat di Indonesia: Analisis Pola Tantangan, Hambatan Kritis, dan Strategi Berkelanjutan: Optimizing Zakat Management in Indonesia: An Analysis of Challenges, Critical Barriers, and Sustainable Strategies - Azwar, Azwar; Khaerul Aqbar (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
The management of zakat in Indonesia plays a significant role in promoting economic equity and the development of the Muslim community, yet its patterns and dynamics of challenges continue to evolve in line with changes in regulations, digital technology, and literacy levels within society. This study aims to analyze the patterns and dynamics of zakat management challenges in Indonesia from various perspectives, to identify critical constraints related to regulations, technology, literacy, and public trust, and to provide strategic recommendations for policymakers and zakat institutions. The research employs a literature review method with a descriptive analytical approach, utilizing various sources and documents related to the development of zakat management in Indonesia. The results reveal that the constraints in zakat management are closely linked to the suboptimal synchronization of regulations and governance, the inadequacy of digital infrastructure and data integration, the low level of zakat literacy, and the underdevelopment of a comprehensive public trust. The implications of these findings can serve as a foundation for policymakers and zakat institutions to formulate adaptive and holistic strategies that enable zakat to function more effectively and sustainably as an instrument for economic equity and the development of the Muslim community.